ASPECTS OF CRIMINAL LAW RELATED TO ERADICATION OF CORRUPTION IN INDONESIA - Ronaldin Fau; Maidin Gultom; Baktiar Simatupang (JURNAL PROINTEGRITA, 2019)
Corruption is a crime that can be said at the position of nadir and has taken root, so that in its eradication it requires seriousness and handling that is very strong. The role of the police, prosecutors and the Corruption Eradication Commission (KPK) law enforcement officers really must be encouraged to handle and prosecute them. So that the formulation of the problem that can be raised is related to the related legal phenomena: 1) How are the legal loopholes that have led to the eradication of corruption in Indonesia ?, 2) What steps can be taken to suppress corruption in Indonesia? And 3) What is the role of law enforcement in dealing with corruption in Indonesia ?. This study uses a normative juridical approach to find legal norms and norms which are criminal law policies in formulating corruption eradication, using primary, secondary and tertiary data as data sources. The method of data collection in a normative juridical approach in this study uses library research techniques (library research). that is by collecting data and conducting library material reviews which consist of laws and regulations, books, law, and other literature related to the problems under study. The results of this study indicate that the discussion of the problem, the Factor in Eradicating Corruption in Indonesia is Not Maximum is a Political Factor Politics is one of the causes of corruption. This can be seen when there is political instability, the political interests of the holders of power, even when reaching and maintaining power. Corrupt behavior such as bribery, money politics is a phenomenon that often occurs, Legal Factors Legal factors can be seen from two sides, on the one hand from the aspect of legislation and the other side is weak law enforcement. The lack of legal substance is easily found in discriminatory and unfair rules; a formulation that is not clear (non lex certa) so that it has multiple interpretations; contradiction and overlapping with other regulations (both equal and higher), Economic Factors Economic factors are also one of the causes of corruption. It can be explained from income or salary that is insufficient, organizational factors Aspects of the occurrence of corruption from the point of view of this organization include: (a) lack of example from the leadership, (b) the absence of the right organizational culture the accountability system in government agencies is inadequate, (d) management tends to cover up corruption within the organization. Strategic steps to tackle corruption are: (1) there must be a joint and public movement (soc, al movement) to eradicate corruption; (2) establishing closer political cooperation in strengthening the anti-corruption political orientation; (3) political parties that are committed to eradicating corruption are needed; (4) carry out reforms to the anti-corruption law so that criminal sanctions can prevent people from committing criminal acts of corruption (5) cooperation between law enforcement officials in conducting investigations and prosecuting the basis of a criminal act of corruption; (6) increasing public oversight of state apparatus; (7) improving public services for the implementation of good and clean governance.